1986
DOI: 10.1128/jb.168.1.123-131.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a plasmid-specified pathway for catabolism of isopropylbenzene in Pseudomonas putida RE204

Abstract: A Pseudomonas putida strain designated RE204, able to utilize isopropylbenzene as the sole carbon and energy source, was isolated. TnS transposon mutagenesis by means of the suicide transposon donor plasmid pLG221 yielded mutant derivatives defective in isopropylbenzene metabolism. These were characterized by the identification of the products which they accumulated when grown in the presence of isopropylbenzene and by the assay of enzyme activities in cell extracts. Based on the results obtained, the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 53 publications
(25 reference statements)
4
69
0
Order By: Relevance
“…In this study, we observed that E. coli harboring pUCA1 forms indigo on 2Ï« YT plates. This phenomenon was reported in the case of naphthalene dioxygenase (14) and cumene dioxygenase (2,12), suggesting that the pUCA1 insert contains genes encoding CARDO. Further sequence analysis of the upstream and downstream regions of carBC will be done to obtain information on the genes encoding CARDO.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we observed that E. coli harboring pUCA1 forms indigo on 2Ï« YT plates. This phenomenon was reported in the case of naphthalene dioxygenase (14) and cumene dioxygenase (2,12), suggesting that the pUCA1 insert contains genes encoding CARDO. Further sequence analysis of the upstream and downstream regions of carBC will be done to obtain information on the genes encoding CARDO.…”
Section: Discussionmentioning
confidence: 91%
“…13) should be taken into consideration when cloning and expressing heterologous aromatic catabolic clusters in this enterobacterium. In this sense, several reports on the cloning and expression of aromatic ring-hydroxylating dioxygenases in E. coli claim that equivalent enzymes from the host could explain the unexpected activities observed when some of the subunits of the cloned dioxygenases were lacking in the recombinant bacteria (82,167,186,305). The described PP-dioxygenase activity of E. coli (see above) could explain some of these unexpected findings.…”
Section: Discussionmentioning
confidence: 98%
“…Barnsley also partially purified from cell extracts an enzyme (isomerase) (Fig. 1, enzyme D trans-4-(3-Hydroxy-2-thianaphthenyl)-2-oxo-but-3-enoate and trans-4-(3-hydroxy-2-benzofuranyl)-2-oxobut-3-enoate were produced by biotransformation of dibenzothiophene and dibenzofuran, respectively, by P. aeruginosa PAO1(pRE654) (11), while trans-4-(3-hydroxy-2-thienyl)-2-oxobut-3-enoate was a product of biotransformation of benzothiophene by P. putida RE204 (13,15 (26) followed by centrifugation to equilibrium through a cesium chloride-ethidium bromide gradient. Plasmid DNA was isolated from E. coli by the method of Holmes and Quigley (29) when recombinants were screened and by the procedure of Clewell and Helinski (6) for largescale preparations.…”
mentioning
confidence: 99%